A comparative study of pH-responsive microcapsules from different nanocomposites. Issue 2 (6th June 2017) - Pentela, Nagaraju; Ayyappan, Vijaya Gowri; Krishnamurthy, Munusamy; Boopathi, Appakutti Achuthan; Rainu, Simran; Sampath, Srinivasan; Mandal, Asit Baran; Samanta, Debasis
Abstract : In this paper, the authors report the preparation of pH-responsive microcapsules using poly(methacrylic acid) and different carbon nanomaterials, graphene oxide (GO) and fullerenol (FOH). Potential non-covalent interactions, as well as a comparative study in terms of stability and structural/morphological aspects of the graphene oxide microcapsules (MGO) and fullerenol microcapsules (MFOH), were carried out using Fourier transform infrared spectroscopy, Raman spectroscopy, thermogravimetric analysis, differential scanning calorimetry analysis, field emission scanning electron microscopy and high-resolution transition electron microscopy. The comparative drug release study for MGO and MFOH was done using ultraviolet illumination, fluorescence spectroscopy and so on. It was observed that the release of the drug (riboflavin) at pH 4 from MGO was faster, reaching the saturation point before 12 h, compared to that in MFOH, where the saturation point was achieved after 18 h. To the best of the authors' knowledge, this is the first report on a comparative study of MGO and MFOH in terms of their stability, pH-responsive nature and other characteristics. This study can be utilized where the carbon nanomaterials (GO/FOH) are used in the preparation of designer microcapsules for targeted drug delivery applications, since the pH varies in different parts of the human body.